PEMBUATAN DAN KUALITAS ARANG AKTIF DARI KAYU SENGON (Paraserianthes falcataria) SEBAGAI BAHAN ADSORBEN - Gustan Pari; Buchari Buchari; Aminudin Sulaeman (Pusat Penelitian dan Pengembangan Hasil Hutan, 1996)
The characterization of activated charcoal from steam activation of sengon (Paraserianthes falcataria) wood is reported in this paper. The purpose of this investigation was to study the influences of temperature and concentration of chemical activator on the activated charcoal yield and its quality. The activated charcoal was produced in a stainless steel retort with electrical heater at the temperature of 7000C, 8000C and 9000C and for activation used NH4HCO3 with its consentration 0,5; 1,0; 3,0; 5,0 and 10% respectively.The best quality of the activated charcoal produced when the activation temperature was 9000C with the NH4HCO3 1,0 %. The yield of activated charcoal was 5,90%, moisturecontent 6,39 %, ash content 9,15 %, volatile matter 8,81 %, fixed carbon 82,04 %. Adsorptive capacity of iodine was 1154,4 mg/g, NH3 25,08 %, CHCl3 42,28 %, CCl4 51,74 %, benzene 49,10% and methylene blue 138,80 - 319,00 mg/g. Surface area was 1143,7 m2/g. The most abundance of particle size was 4,00 - 5,65 micron and pore volume 16,00 - 22,62 micron. High and diameter pore was 37,49 and 22,52 micron.